The prevalence of hypertensive complications of pregnancy in Dora Nginza Hospital, Port Elizabeth, Eastern Cape - Odufuwa, Olywatoyin Aliu (Stellenbosch : Stellenbosch University, 2016)
BACKGROUND: Hypertension and its complications is responsible for a significant proportion of maternal and neonatal morbidity and mortality worldwide. In Dora Nginza Hospital, clinical experience has shown that hypertension and its complications are common but despite this assumption, the overall prevalence of complications, social and demographic characteristics and various forms of presentations of hypertension in pregnancy is still largely unknown. OBJECTIVES: To determine the prevalence of complications, risk factors, social and demographic characteristics of hypertensive complications of pregnancy in Dora Nginza Hospital. STUDY DESIGN: The study is a retrospective descriptive study performed on medical records. The study was carried out by looking at records of patients admitted with hypertension in pregnancy over a 2 year period (2007-2008). MS Excel was used to capture the data and STATISTICA version 9 was used for data analysis.